Essential advances in surgical and adjuvant therapies for colorectal cancer 2018‐2019. Issue 1 (28th January 2020) - Akagi, Tomonori; Inomata, Masafumi
Abstract: Surgical resection and adjuvant chemotherapy are the only treatment modalities for localized colorectal cancer that can obtain a "cure." The goal in surgically treating primary colorectal cancer is complete tumor removal along with dissection of systematic D3 lymph nodes. Adjuvant treatment controls recurrence and improves the prognosis of patients after they undergo R0 resection. Various clinical studies have promoted the gradual spread and clinical use of new surgical approaches such as laparoscopic surgery, robotic surgery, and transanal total mesorectal excision (TaTME). Additionally, the significance of adjuvant chemotherapy has been established and it is now recommended in the JSCCR (the Japanese Society for Cancer of the Colon and Rectum) guideline as a standard treatment. Herein, we review and summarize current surgical treatment and adjuvant chemotherapy for localized colorectal cancer and discuss recent advances in personalized medicine related to adjuvant chemotherapy. Abstract : Patients with colorectal cancer considered to be curative now have several options for surgical approaches, adjuvant chemotherapy regimens, and duration of therapy. Although the current situation makes it difficult for oncologists and patients to make clinical decisions, future developments are expected to lead to more effective personalized medicines and treatment.